GOVERNMENT CONSISTENCY IN ENFORCEMENT OF REGULATIONS REGARDING MINERAL AND COAL MINING RELATED TO MINE RECLAMATION - Husni Thamrin; Aji Titin Roswitha Nursanthy; Leonito Ribeiro; Linda Afriani (Awang Long Law Review, 2023)
Reclamation is an activity that aims to improve or manage the use of disturbed land as a result of mining business activities so that it can function and have the power to function according to its designation. excavated. For this reason, the government has issued Government Regulation Number 78 of 2010 concerning Post-Mining Reclamation Decree and Regulation of the Minister of Energy and Mineral Resources (ESDM) Number 26 of 2018 concerning Implementation of Good Mining Principles and Supervision of Mineral and Coal Mining. The purpose of issuing these two regulations is very clear, so that the negative impacts of mining activities can be reduced or even eliminated. Various productive efforts on ex-mining land by carrying out reclamation and utilizing it as an ecotourism area. Utilizing part of it as a fish farming pond and the rest being used as a model of a biological conservation forest with proboscis monkeys and various kinds of birds as the key space is one of the efforts to restore nature's preservation. The research method used is normative or doctrinal legal research. Normative legal research or doctrinal legal research, which is also referred to as library research or document study, is research that is carried out or aimed only at studying written regulations or other legal materials. The result of research reclamation is an activity to restore the ecosystem so that it can function again as before. While Post-mining Activities are activities to repair ex-mining land to restore environmental functions and social functions according to local conditions throughout the mining area.